The Technical University Teacher: What Do Students Value? - T. Yu. Polyakova (Высшее образование в России)
At present, according to Presidential Address to the Federal Assembly our country has set the task of reforming higher education based on the synthesis of the best practices of the Soviet educational system and the experience of recent decades. This increases the responsibility of technical university teachers, whose competencies have been determined in recent years on the basis of different scientific approaches. In this regard, the problem of identifying the teachers’ qualities that are significant for students is becoming especially relevant.In order to solve the problem, the research of students’ essays obtained as a result of the International Essay Contest in English “My University Engineering Teacher I will Never Forget” was undertaken. The contest was organized by Moscow Automobile and Road Construction State Technical University (MADI) in 2021-22. The hypothesis of the research suggested that the personality traits of the technical university teacher are valued by students not lower than their professional competencies.In order to achieve the goal and verify the hypothesis, four tasks were set and solved during the research: the students’ opinions on the role of the teacher were revealed; the professional competencies of the teacher that are significant for students were determined; the personality traits of the teacher that are significant for students were determined; the significance of the teacher’s professional competencies and personality traits for students was compared. The research methodology provided for qualitative and quantitative evaluation of the students’ essays including their content analysis.The paper describes the main results of the research, which confirmed the hypothesis, as well as their interpretation. The interpretation of the research results allowed us to draw general conclusions concerning reforming the modern system of engineering education. The main conclusion concerns the necessity of returning engineering education to the traditional for the Soviet higher school integration of education and upbringing and the significance of developing in the educational process not only the competencies relevant for employers, but also the personality of future specialists.